Telefonica : a lean elephant - Chesbrough, Henry; Apruzzese, Susan Jurado; de Olano Mata, Maria (London : SAGE Publications Ltd, 2017)
This case shows Telefonica, a large and sophisticated technology company in Spain, try to transform its innovation process. To do so, it is employing Lean Startup techniques. The case provides a detailed look at the companys efforts in this regard, showcasing not only some of the successful outcomes that were realized, but also some of the organizational challenges that have been encountered along the way. As Lean Startup becomes more widespread in the entrepreneurial community, it is spilling over into the corporate world as well. But as this case demonstrates, there are important contextual differences in employing Lean Startup techniques inside a much larger company.
Originally published: Chesbrough, H., Juardo Apruzzese, S., & de Olano Mata, M. (2016). Telefonica: A lean elephant. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Telefonica; High technology industry -- Spain -- Case studies; New business enterprises -- Spain -- Case studies; Small business -- Growth -- Spain -- Case studies